Spatial distribution of poverty incidence in Peninsular Malaysia - Vaziri, Mehrdad (2012)
The purpose of this study is to find out the spatial distribution of poverty incidence in Peninsular Malaysia and the type of relationship the poverty distribution has with different factors. Hot spot analysis has been applied in this study to find out where the poor people are clustered by using Zone of Indifference method and distance band of 21000 meters. Geographically Weighted Regression (GWR) was used to examine the type of relationship Standardized Poverty Rate (SPR) have with three explanatory variables of percentage of Non Primary Agricultural Area (NPAA)in each mukim, Road Density of each mukim, and Distance between mukim centroids and district capital city. All of the analyses were done by using ArcGIS10.0 software. The research found out that there are hot spots of poor people located in North East of Peninsular Malaysia in Kelantan and Terengganu states. There were positive and negative correlations between different variables and SPR and the type and quality of relationship is changing throughout the whole Peninsular Malaysia. The negative values in GWR maps show negative correlations and the higher negative value there is the stronger negative correlation is there. The positive values in GWR maps show positive correlations and the higher the value is the stronger positive relationship is.